Bubble Thy Neighbor: Portfolio Effects and Externalities from Capital Controls - Roland Straub; Kristin Forbes; Marcel Fratzscher; Thomas Kostka (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2013)
We use changes in Brazil s tax on capital inflows from 2006 to 2011 to test for direct portfolio effects and externalities from capital controls on investor portfolios. The analysis is structured based on information from investor interviews. We find that an increase in Brazil s tax on foreign investment in bonds causes investors to significantly decrease their portfolio allocations to Brazil in both bonds and equities. Investors simultaneously increase allocations to other countries that have substantial exposure to China and decrease allocations to countries viewed as more likely to use capital controls. Much of the effect of capital controls on portfolio flows appears to occur through signalling i.e. changes in investor expectations about future policies rather than the direct cost of the controls. This evidence of significant externalities from capital controls suggests that any assessment of controls should consider their effects on portfolio flows to other countries.
Keywords: F32; F42; G11; 330